Pengaruh Pemberian Zat Pengatur Tumbuh NAA dan IBA Terhadap Pertumbuhan Semai Cabutan Tumih [Combretocarpus rotundatus (Miq.) Danser] - Istomo Istomo; Fauzi Kiswantara (Jurnal Silvikultur Tropika, 2012)
The Influence of Plant Growth Regulators NAA and IBA on the Growth of Stump Seedling of Tumih [Combretocarpus rotundatus (Miq.) Danser]Tumih which has a Botany name Combretocarpus rotundatus is one of the species that lives in peat swamp forests. C. rotundatus often found in secondary forests or forests with open canopies. Nowadays deforestation often occurs in Indonesia, it is feared this species will be decrease and lead to scarcity of it in natural forest. C. rotundatus also have characteristic that suit for plan in effort to initiate rehabilitation of agitated peatlands. Efforts to propagate this species was applied by the stump method. The research conducted aims to determine the life and growth of tumih by giving the Plant Growth Regulators. The results showed that the percentage of life that is obtained for NAA at 66.67%, 68.89% of IBA, NAA and IBA combination of 71.11% and 64.44% for controls. Other factors that may affect it is initial height of plants and environmental conditions in research.